2021
DOI: 10.18176/jiaci.0673
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Epigenetics of Nasal Polyposis: A Systematic Review

Abstract: Chronic rhinosinusitis (CRS) is an inflammatory disease of the nose and paranasal sinuses, often associated with nasal polyps (CRSwNP) in the most severe cases. Like other complex diseases, genetics are thought to play an important role in the risk and development of the disease, and the environment may also contribute to modulate the epigenetic signature in the patients. In the present systematic review, we aimed at compiling all the published data about genetic and epigenetic variations in CRSwNP since 2000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…3,4 Thus, without changing the genotype, epigenetic mechanisms change the individual's phenotype (observable characteristics and traits of an individual, including disease activity, severity, subtype that are determined by genotype and environmental factors). The common mechanisms involved in epigenetics are DNA methylation, histone modifications, non-coding RNAs 5,6 and alternative polyadenylation. 7 CpG sites are regions of DNA where a cytosine nucleotide is followed by a guanine nucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Thus, without changing the genotype, epigenetic mechanisms change the individual's phenotype (observable characteristics and traits of an individual, including disease activity, severity, subtype that are determined by genotype and environmental factors). The common mechanisms involved in epigenetics are DNA methylation, histone modifications, non-coding RNAs 5,6 and alternative polyadenylation. 7 CpG sites are regions of DNA where a cytosine nucleotide is followed by a guanine nucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…These were clustered into 8 main networks, linking genes involved in inflammation and immune response (e.g., MHC), cytokine genes (e.g., TNF), leukotriene metabolism, and the extracellular matrix. Eighty-nine miRNAs were also identified, associated mainly with the cell cycle, inflammation, and the immune response ( 37 ).…”
Section: Other Risk Factors For Late Onset T2 Eosinophilic Asthmamentioning
confidence: 99%
“…Currently, the only fully proven genetic cause of CRS is a genetically determined ciliary impairment, as seen in patients with Kartagener's syndrome and primary ciliary dyskinesia (PCD), as well as nasal mucus dysfunction in cystic fibrosis (CF). Recent studies focusing on genetic and epigenetic aspects of nasal polyposis link this medical condition with genes involved in inflammation and immune response, cytokine genes, leukotriene metabolism, and the extracellular matrix [3]. Some of them have shown that abnormalities in the mobility and the activity of the ciliated epithelium of the upper respiratory tract may be related to the bitter taste receptors (T2Rs): TAS2R13, TAS2R19, TAS2R38, and TAS2R49 [4,5], out of which, TAS2R38 seems to have major significance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%